Crocus sativus L. versus Citalopram in the Treatment of Major Depressive Disorder with Anxious Distress: A Double-Blind, Controlled Clinical Trial - Ghajar, A.; Neishabouri, S. M.; Velayati, N.; Jahangard, L.; Matinnia, N.; Haghighi, M.; Ghaleiha, A.; Afarideh, M.; Salimi, S.; Meysamie, A.; Akhondzadeh, S. (Pharmacopsychiatry, 2017)
Introduction: Saffron (Crocus sativus L.) has demonstrated antidepressant effects in clinical studies and extensive anxiolytic effects in experimental animal models.Methods: 66 patients with major depressive disorder accompanied by anxious distress were randomly assigned to receive either saffron (30 mg/day) or citalopram (40 mg/day) for 6 weeks. Hamilton Rating Scale for Depression (HAM-D) and Hamilton Rating Scale for Anxiety (HAM-A) were used to assess treatment effect during the trial.Results: 60 participants finished the study. Patients who received either saffron or citalopram showed significant improvement in scores of the Hamilton Rating Scale for Depression (P-value<0.001 in both groups) and Hamilton Rating Scale for Anxiety (P-value<0.001 in both groups). Comparison of score changes between the 2 trial arms showed no significant difference (P-value=0.984). Frequency of side effects was not significantly different between the 2 groups.Discussion: The present study indicates saffron as a potential efficacious and tolerable treatment for major depressive disorder with anxious distress.
Keywords: anxious distress; citalopram Crocus sativus; major depressive disorder